Determination of chlorinated paraffins in PM2.5 by QuEChERS combined with ultra-high performance liquid chromatography-quadrupole/orbitrap high resolution mass spectrometry - Wenyan YAN; Chao WANG; Juan LIU; Yibin SUN; Wen GU; Yifu LU; Ke FANG; Yi WAN; Song TANG (环境与职业医学)
BackgroundPrevious research on chlorinated paraffins (CPs) in fine particulate matter (PM2.5) has predominantly focused on short- and medium-chain chlorinated paraffins (SCCPs and MCCPs), and few studies could simultaneously determine short-, medium-, and long-chain chlorinated paraffins (LCCPs). Simultaneous extraction and determination of SCCPs, MCCPs, and LCCPs in PM2.5 could provide technical support for their environmental monitoring and human health risk assessment.ObjectiveTo establish a method based on QUEChERS pretreatment method in conjunction with ultra-performance liquid chromatography-quadrupole/orbitrap high resolution mass spectrometry for simultaneously determining the levels of SCCPs, MCCPs, and LCCPs in PM2.5. MethodsThe extraction solvents, extraction salts, and extraction steps of a QuEChERS method were optimized. The extraction efficiencies of the target substances were compared under 4 extraction solvents [acetonitrile, dichloromethane, and n-hexane solvents in sequence; acetonitrile: dichloromethane: n-hexane = 1: 1: 2 (v/v/v) mixed solvent; 1% acetic acid-acetonitrile: dichloromethane: n-hexane = 1: 1: 1 (v/v/v) mixed solvent; acetonitrile: dichloromethane: n-hexane = 1: 1: 1 (v/v/v) mixed solvent], 2 dehydrated salts (anhydrous MgSO4+NaCl and anhydrous Na2SO4+NaCl), 2 purification salts (C18 and PSA), and 4 vortex time (5, 7.5, 10, and 12.5 min) conditions. Then internal standard was utilized to estimate linear range and detection limit of the refined QuEChERS approach. ResultsThe linearities of SCCPs, MCCPs, and LCCPs were good in the range of 10~1000 ng·mL−1 with the correlation coefficients all greater than 0.96. The method detection limits (MDLs) ranged from 0.01 to 0.29 ng·m−3. The spiked recoveries of SCCPs, MCCPs, and LCCPs at the low, medium, and high concentrations were 77.38%-81.64%, 93.11%-99.78%, and 87.41%-101.39%, respectively, and the relative standard deviations (RSDs) were 2.90%-12.84%. This method was used to determine the CPs levels in 11 PM2.5 samples from Shijiazhuang. The positive rates of ∑SCCPs, ∑MCCPs, and ∑LCCPs were all 100%, the concentration ranges were 0.24-2.18 ng·m−3 (mean 0.84 ng·m−3), 0.17-1.67 ng·m−3 (mean 0.70 ng·m−3), and 0.01-0.16 ng·m−3 (mean 0.04 ng·m−3), respectively, and the percentages to ΣCPs were 52.95%, 44.39%, and 2.66%, respectively. ConclusionThe method established in this study is simple, time-saving, solvent saving, and can simultaneously detect SCCPs, MCCPs, and LCCPs in PM2.5, which is suitable for the determination of PM2.5 samples in large quantities, and can also provide a reference for the detection methods of other halogenated organic compounds in PM2.5.